The Assistance for Learning English Vocabulary Using Finger Puppets - Hesty Widiastuty Widiastuty; Sri Normuliati Normuliati; Yunus Firmansah Firmansah; Siska Indriyani Indriyani; Nur Melani Yuliana Yuliana (Jurnal Inovasi Pengabdian Masyarakat Pendidikan, 2024)
In teaching the language, they need effective media. It can improve the ability of learners to learnability. In addition, using media can make learning more interesting and exciting, resulting in better material retention. These finger puppets can be an alternative medium in language learning. In addition, finger puppets are perfect for educational games because they are easier to move according to the storyline and increase vocabulary. The purpose of this community service activity is to introduce the use of finger puppets as a medium in vocabulary learning. The vocabulary used is based on the folklore used entitled, "The Tale of Bawang Merah & Bawang Putih". By doing storytelling with finger puppets, students are expected to be able to understand and capture the vocabulary in the story and the use of finger puppets can attract their interest in learning the language. The method is divided into four stages: preparation, implementation, evaluation, and report preparation. The result of this activity is that participants become more active in interacting in class during the teaching and learning process; their vocabulary increases; their vocabulary mastery improves as a result of the given vocabulary exercises; and the participants' interest in learning English increased as a result of their interest in watching interesting and engaging finger puppet shows.